The use of taxonomic families as biological surrogates of the diversity of the Amazonian stream fish. (August 2022) - Santos, Luciana Lameira dos; Benone, Naraiana Loureiro; Brasil, Leandro Schlemmer; Pires, Tiago H.S.; Begot, Tiago Octavio; Dantas, Danihelton Douglas F.; Montag, Luciano Fogaça de Assis
Highlights: Taxonomic families have high potential as surrogates of stream fish diversity. Cichlidae and Lebiasinidae are potential diversity surrogates in six Amazon basins. Crenuchidae and Hypopomidae were good diversity surrogates in floodplain basins. Characidae, Gymnotidae, Rivulidae were good diversity surrogates in upland basins. Abstract: The reliable identification of the fish species found in Amazonian streams requires a considerable investment of both time and resources, which often hampers the biodiversity pattern mapping and conservation planning. This problem can be overcome using biological surrogates such taxonomic families, this would reduce the number of fish to be identified and thus facilitate the development of studies. The present study analyzes the potential of families as surrogates of the fish diversity of Amazonian streams. For this, we verified the degree of congruence between the distribution of species organized by family and the composition of the assemblage in two different spatial scenarios. At the biome scale, we verified the degree of congruence in the fish faunas of 54 streams located within six drainage basins in Brazilian Amazonia. At the regional scale, we compared the data from the basins located on the lowland floodplain and those at higher altitudes. The Cichlidae and Lebiasinidae were identified as potential biological surrogates at both spatial scenarios, demonstrating more than 80% similarity with species matrix in all the analytical approaches. The families Crenuchidae and Hypopomidae were the most congruent with the fish from the floodplain basins, both were more than 80% congruent with the species matrix. In upland basins, Characidae, Gymnotidae and Rivulidae were highly similar to the species matrix, in particular Gymnotidae and Rivulidae with more than 90% similarity. Overall, we can conclude that the biological surrogacy approach is a potentially valuable alternative for species diversity evaluation of Amazonian streams ecosystems, considering the accelerated loss of the diversity of these systems.